A Novel Group-based Correlation for the Ignition Delay Time of Paraffinic-type Fuels. Issue 1 (2nd January 2022) - Hernández, Juan J.; Lapuerta, Magín; Cova-Bonillo, Alexis
ABSTRACT: A group contribution equation is proposed for the prediction of the cool flame and main auto-ignition delay time for linear and slightly branched paraffinic fuels. The experiments were carried out in a constant volume combustion bomb where pressure and temperature were modified for five linear paraffinic hydrocarbons (n-C10, n-C12, n-C14, n-C16 and n-C18) and three C16 isomers with different degree of branching (2-methylpentadecane; 2, 6, 10-trimethyltridecane and 2, 2, 4, 4, 6, 8, 8-heptamethylnonane). An Arrhenius-type correlation is proposed, with extended parameters to the number of groups CH3, CH2 and CH and the equivalence ratio. The proposed equation has enough accuracy to estimate the autoignition delay times of paraffinic fuels (from n-dodecane to n-octadecane) for temperature ranging from 535 to 650ºC and pressure from 11 to 21 bar.